1985
DOI: 10.3109/08923978509047632
|View full text |Cite
|
Sign up to set email alerts
|

The Influence on the Formation of Unstable Haemoglobin by the Immunomodulating 2-Cyanaziridines Azimexone and Bm 41.332 in Mice

Abstract: Azimexone causes in mice the formation of unstable haemoglobins after a single dose of 20 mg/kg. BM 41.332, another immunomodulating drug of the 2-cyanaziridine class, induces these unstable haemoglobins only after a single oral administration of 500 mg/kg. Subsequently to the formation of unstable haemoglobins we observed a development of Heinz bodies. These effects of the 2-cyanaziridines were elicited neither by methaemoglobin formation nor by an impairment of the components protecting haemoglobin against o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Animal studies showed only a specific toxic reaction of ciamexon with hemoglobin, leading t o its instability and to the formation of Heinz bodies in the red blood cells of treated mice (23) and an increased, dose-dependent susceptibllity t o toxic hemoglobinopathies in rats and dogs (2.3). Thus, our study substantiates the influence of ciamexon on the clinical features and the immunocellular response in RA, but it also demonstrates the agent's potential toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed only a specific toxic reaction of ciamexon with hemoglobin, leading t o its instability and to the formation of Heinz bodies in the red blood cells of treated mice (23) and an increased, dose-dependent susceptibllity t o toxic hemoglobinopathies in rats and dogs (2.3). Thus, our study substantiates the influence of ciamexon on the clinical features and the immunocellular response in RA, but it also demonstrates the agent's potential toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…), with the Correspondence: Dr B. K. Park, Department of Pharmacology and Therapeutics, University of Liverpool, P.O. Box 147, Liverpool L69 3BX formation of Heinz bodies (Isert et al, 1985;1987).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat, [14C]-ciamexon (Isert et al, 1987) and a related compound, azimexone (Wolfel et al, 1981) are cleared rapidly from plasma. The aziridine ring is reactive toward sulphur nucleophiles such as cysteine (Bicker, 1984) and cellular glutathione (Hata et al, 1988) formation of Heinz bodies (Isert et al, 1985;1987).…”
Section: Introductionmentioning
confidence: 99%